Attitudes among International University Students in Delivering English Oral Presentation in Academic Settings - Benraghda, Abdelmadjid; Zuraina, Ali; Noor Raha, Mohd Radzuan (IJEE, 2015)
This paper outlines, in the pilot study, the results of a survey that carried out so as to identify the international university students’ attitudes in delivering oral presentation in English language in academic settings. 30 non-English major university students who were targeted, in this research, to figure out what attitudes had pertaining to English oral presentation. They were divided into three groups according to their ages. Frequency and ANOVA were used in analyzing the data. The study indicates that students are willing to deliver an oral presentation in English language. They intend to be involved in various activities related to oral presentation in English language as well. However, students were almost reluctant to reveal a plain attitude towards presenting in English language. Also, it is found that, there is no statistically significant difference in their attitudes based on their ages in delivering oral presentation in English language in academic context.